Nanoscale metal–organic frameworks as photosensitizers and nanocarriers in photodynamic therapy - Matlou, Gauta Gold; Abrahamse, Heidi (Frontiers in Chemistry, 2022)
Photodynamic therapy (PDT) is a new therapeutic system for cancer treatment that is less invasive and offers greater selectivity as compared to chemotherapy, surgery, and radiation therapy. PDT employs irradiation light of known wavelength to excite a photosensitizer (PS) agent that undergoes photochemical reactions to release cytotoxic reactive oxygen species (ROS), that could trigger apoptosis or necrosis-induced cell death on tumor tissue. Nanoscale metal-organic frameworks (NMOFs) possess unique structural advantages such as high porosity, large surface area and tunable compositions that has attracted attention towards their use as photosensitizers or nanocarriers in PDT. They can be tailored for specific drug loading, targeting and release, hypoxia resistance and with photoactive properties for efficient response to optical stimuli that enhances the efficacy of PDT. In this review, an overview on the basic chemistry of NMOFs, their design and use as photosensitizers in PDT and as nanocarriers in synergistic therapies is presented. The review also discusses the morphology and size of NMOFs and their ability to localize within a targeted tissue for effective and selective cancer cell death over healthy cells.